Propuesta de aprovechamiento de los recursos biológicos y residuos sólidos en el centro poblado de Nina Rumi – San Juan-Iquitos-Loreto – Maynas 2021 - Villacorta Salazar, Anthonny Arnolds (2022)
This study was carried out in Nina Rumi population center, district of San Juan, Province of Maynas, located 25 km from Iquitos on the right bank of Nanay River, whose purpose was to be able to propose the use of resources biological and solid waste in the population of the town of Nina Rumi, so that awareness can be generated in such a way that it learns to manage and conserve them, knowing that these issues improve the economic conditions and therefore the social well-being of the population. From the obtained results, it can be seen that the average production of organic waste from Nina Rumi farmhouse is 2,19 per kg / day / family, which corresponds to 0.409 kg per person / day. The population of the populated center of Nina Rumi can produce up to 105,99 mt / year. The cost of production of the compost is 0,70 Soles / kg and the cost of sale is 2,0 / kg. The economic indicators are all favorable for investment in the proposed proposal. The TIR is profitable since the K is greater than 10% therefore. The B / C = 1 indicates that for every single invested a profit of 0,32 ct Soles is obtained, being a profitable business.